2006
DOI: 10.1158/1535-7163.mct-05-0210
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac independently modulates extracellular signal–regulated kinase 1/2 and cyclic GMP–dependent protein kinase signaling pathways

Abstract: Colorectal cancer is the second leading cause of cancer mortality in the United States. Substantial human and animal data support the ability of nonsteroidal antiinflammatory drugs to cause regression of existing colon tumors and prevent new tumor formation. The mechanism by which the nonsteroidal anti-inflammatory drug sulindac prevents tumor growth is poorly understood and seems complex as sulindac can modulate several growth-related signaling pathways. Sulindac metabolites simultaneously (a) increase cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…The kinetics of CCK's anorectic action are similar to that of amylin (51,59); however, because the target site in the present study was the AP and not the NTS, as in the studies by Sutton and colleagues (58,59), the uptake of U0126 and duration of inhibitor activity may differ between the two brain areas. Furthermore, cell culture studies have shown that U0126 effectively blocked ERK1/2 phosphorylation as early as after 30 min of incubation with U0126 in colon cancer cells (48). In parallel, the effect of amylin dosage was also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of CCK's anorectic action are similar to that of amylin (51,59); however, because the target site in the present study was the AP and not the NTS, as in the studies by Sutton and colleagues (58,59), the uptake of U0126 and duration of inhibitor activity may differ between the two brain areas. Furthermore, cell culture studies have shown that U0126 effectively blocked ERK1/2 phosphorylation as early as after 30 min of incubation with U0126 in colon cancer cells (48). In parallel, the effect of amylin dosage was also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDS are well studied class of chemopreventive agents and have been shown to act through both COX dependent 19,20 and independent pathways. 21,22 Rofecoxib and celeocoxib were introduced into the market as selective COX-2 inhibitors with nongastrointestinal side effects, but their prolonged use has raised concern about their adverse cardiovascular effects. 23 Since the use of these agents for cancer therapy has not been fully evaluated, understanding the underlying mechanisms of these agents can lead to further development of novel therapeutic agents for PC utilizing the nonsteroidal scaffolds such as COX-2 inhibitors.…”
mentioning
confidence: 99%
“…The growing evidence has indicated that sulindac targets nuclear β-catenin accumulation and Wnt signaling in colorectal cancers in vivo and in vitro (Boon et al, 2004;Chang et al, 2005;Gardner et al, 2004;He et al, 1999;Koornstra et al, 2005;Rice et al, 2003;Rice et al, 2006), but that sulindac targeting β-catenin in other sites is rare. Even recent report indicated that NSAIDs inhibition of β-catenin required the high level expression of peroxisome proliferators-activated receptor γ (PPAR-γ) and its co-receptor retinoid-X-receptor α (RXR-α) (Lu et al, 2005), how they are interacting to the response to NSAIDs remains unclear and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%